Begomovirus yang Berasosiasi dengan Gejala Mosaik Kuning pada Tanaman Terung di Bengkulu : Begomovirus Associated with Yellow Mosaic Symptom on Eggplant Plant in Bengkulu - Nabillah, Ade; Alamria, Intan Suryani; Sari, Icha Kurnia Nanda; sutrawati, mimi; Bustamam, Hendri (Jurnal Fitopatologi Indonesia, 2024)
Eggplant (Solanum melongena) is a horticultural crop that has high economic value and is widely cultivated. One of the obstacles to eggplant cultivation is virus infection that causes diseases. In several eggplant fields in Bengkulu, systemic symptoms of yellow mosaic were found which were similar to Begomovirus infection in chilies. Research was conducted to detect and identify Begomovirus as the causal agent of yellow mosaic symptoms on eggplant plants in Bengkulu and its association with betasatellites. Samples were taken by purposive sampling from eggplant fields in Bengkulu City, Central Bengkulu Regency, North Bengkulu Regency, Kepahiang Regency, and Rejang Lebong Regency. Virus detection was carried out by PCR method using Begomovirus universal primers and betasatellite specific primers followed by confirmation of virus identity by DNA sequencing. PCR using universal Begomovirus and betasatellite primers was successfully amplified DNA fragments measuring ±912 bp and ±1300 bp, respectively from leaf samples with symptoms of yellow mosaic, leaf malformation and thickening of leaf veins. Based on DNA sequencing, samples from North Bengkulu and Kepahiang showed the highest homology 99% with Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV) from Indonesia, Malaysia and Thailand. These findings are the first reports of TYLCKaV infection and its association with Begomovirus betasatellites on eggplant in Bengkulu.